Qualitative analysis of water supply of Kyiv - Vasilenko, Lesya; Zhukova, Olena; Bereznitska, Julia (My University, 2018)
Today, a very urgent task is to analyze the water supply and quality of drinking water in Ukraine, the development of new normative documents, the improvement of existing water treatment technologies with the approximation of the standards of European countries. We based on the example of Kyiv conducted a preliminary analysis of the quality of water used for centralized water supply. The paper summarizes real hydrological information on surface water supply sources over a five-year period (the Kyiv Reservoir and the Desna River), data on the qualitative assessment of surface waters (ecological index, water pollution index), cause-and-effect relationships of environmental equilibrium, primary sources of pollution and pollutants, an analysis of the dynamics of water pollution, as well as the characteristics and volumes of discharges of pollutants Dnieper and Desnyanskaya water stations.
Keywords: qualitative depletion; quantitative depletion; environment; nature management; water pollution index; ecological index.